Recent Publications (Quarterly Journal of Economics, 1969)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 83, Issue 2, May 1969, Pages 349–351, https://doi.org/10.1093/qje/83.2.349 Published: 01 May 1969